Menu evaluation based on rough MAIRCA and BW methods - Arsić, Slaviša N.; Pamučar, Dragan; Suknovic, Milija; Janošević, Miljojko (Serbian Journal of Management, 2019)
The evaluation of dishes represents basic activity in the structuring of menu, which allows the optimal use of resources in order to fully satisfy the expectations of users and restaurant management. This study presents a new approach in menu evaluation using the MultiAttributive Ideal-Real Comparative Analysis (MAIRCA) method, modified by application of rough numbers in dealing with imprecisions in group decision making and the Best-Worst Method (BWM) for determining the interval values of weight coefficients which objectivize the inconsistencies in expert judgment. The model was successfully tested on the menu of a collective nutrition restaurant, where the evaluation of six existing breakfast dishes and a new dish that should replace the worst ranking dish was carried out. Validation of the model was done by comparing the results obtained by application of MABAC and VIKOR methods, which confirmed high reliability. The validated values were discussed in sensitivity analysis, through 27 scenarios with the change in value of weight coefficients, which showed a large correlation of the obtained ranks and confirmed credibility of the obtained values.